PENEGAKAN HUKUM TERHADAP PELAKU PENGANIAYAAN HEWAN DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - Eliyani Esther Marlina; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
At this time, there are many cases of torture or killing of animals in inhuman ways. Abuse of animals is not only considered to violate moral ethics but also against positive law, because animal abuse is regulated in the laws and regulations in Indonesia. However, the implementation of the rules on animal mistreatment is still not fully implemented due to the lack of strict law enforcement given to the perpetrators of animal abuse and the lack of public knowledge and awareness of the rules related to animal mistreatment. Some cases of animal abuse that have occurred in Indonesia have only been reported. Apart from that, of the many cases of animal abuse that occurred in Indonesia, only two cases ended up being decided by the court. In Riau Province, there have also been many cases of animal abuse, both light treatment of animals in the form of neglect of animals to severe abuse of animals that cause deathThis research is a juridical empirical research or sociological legal research. Empirical juridical research is carried out by identifying the law and how the effectiveness of the law applies in society, because in this study the author directly conducted research at the location or place under study, namely the Riau Regional Police. This research is descriptive in nature, which is to provide a clear and detailed description of the problems researched by researchers, namely the Law Enforcement of Animal Abuse in Riau Regional Police. Sources of data used in this study are primary data, secondary data and tertiary data. Data collection techniques in this study were interviews and literature review.From the results of the research carried out, it can be concluded that law enforcement against perpetrators of animal abuse in the Legal Area of the Riau Regional Police has not run optimally due to the lack of seriousness by law enforcement officials to follow up on perpetrators of animal abuse. Obstacles in enforcing the law on animal mistreatment are the absence of regulations on animal mistreatment due to the low threat of criminal sanctions, the lack of seriousness of law enforcement officials and the lack of public knowledge regarding the crime of animal mistreatment Efforts taken to overcome these obstacles are by reformulating regulations related to giving heavier criminal sanctions, holding outreach and outreach to the public and increasing the capacity and seriousness of law enforcers.Keywords: Law Enforcement-Crime- Animal Abuse